Insulin sensitisation affects lipoprotein lipase transport in type 2 diabetes: role of adipose tissue and skeletal muscle in response to rosiglitazone. - Tan, G; Olivecrona, G; Vidal, H; Frayn, K; Karpe, F (2006)
AIMS/HYPOTHESIS: Lipoprotein lipase (LPL) is produced by adipose tissue and skeletal muscle, but acts on plasma lipoproteins after being transported to endothelial binding sites. Insulin resistance is associated with decreased plasma LPL mass. We investigated the effects of insulin sensitisation on tissue-specific LPL expression and transport in patients with type 2 diabetes. MATERIALS AND METHODS: Arterio-venous gradients of plasma LPL activity and mass across adipose tissue and skeletal muscle were measured in 16 type 2 diabetic patients in a double-blind, placebo-controlled, cross-over randomised trial of rosiglitazone. In vivo LPL rate of action was assessed by tissue-specific arterio-venous triglyceride concentration gradients. LPL mRNA was quantified in adipose tissue and skeletal muscle biopsies. RESULTS: Adipose tissue released large quantities of inactive LPL (p<0.001); skeletal muscle released small amounts of active LPL (p<0.01). Rosiglitazone increased adipose tissue release of LPL mass (+35%, p=0.04) and decreased the release of active LPL from skeletal muscle (-57%, p=0.03). Rosiglitazone increased adipose tissue and skeletal muscle LPL mRNA, but did not affect adipose tissue LPL rate of action or activity. Adipose tissue release of LPL mass correlated with systemic LPL mass concentrations (r=0.47, p=0.007), suggesting that the rate of adipose tissue release of LPL mass is a major determinant of systemic LPL mass concentrations. CONCLUSIONS/INTERPRETATION: LPL transport from adipose tissue and skeletal muscle are regulated differently. In adipose tissue, rosiglitazone increases LPL mRNA abundance and LPL transport rate and possibly increases endothelial binding sites for LPL, but affects neither tissue LPL activity nor LPL rate of action.